Clinical-pathological Profile of Colorectal Adenocarcinomas with APC, PIK3CA and SMAD4 Mutations in Uganda - Wismayer, Richard; Mathews, Rosie; Whalley, Celina; Kiwanuka, Julius; Kakembo, Fredrick Elishama; Thorn, Steve; Wabinga , Henry; Odida, Michael; Tomlinson, Ian (Medical Research and Its Applications Vol. 5, 2024)
Introduction: APC gene mutations are an important initiator in tumorigenesis and have been detected in many colorectal cancers (CRC). There is conflicting evidence regarding the association between clinicopathological features of CRC and PIK3CA mutations. A promising prognostic factor of CRC and an important molecule to understand the progression and tumorigenesis of CRC is the SMAD family member 4 (SMAD4). The frequency rates of APC, PIK3CA, and SMAD4 mutations in CRC differ among populations. The objective of this study was to determine the mutation frequencies and determine their association with certain clinicopathological features in Ugandan patients. Methodology: A cross-sectional study between 2008 to 2021 involving four hospitals in central Uganda and the Department of Pathology, School of Biomedical Sciences, College of Health Sciences, Makerere University. The demographics, stage, grade, LVI status and histopathological subtype were obtained for each CRC participant. The CRC tumours were evaluated using next-generation sequencing (NGS). The pathological mutation rates of APC, PIK3CA and SMAD4 were recorded, along with clinicopathological features. The chi-square test and Fischer’s exact test were used to determine the association between clinicopathological features and mutation status. Results: Out of 127 CRC participants, the mutation rates were APC: 77(60.6%), PIK3CA: 37(29.1%) and SMAD4: 68(53.5%). A loss of APC was found in 70.2% of female participants compared to 29.8% of female participants with the presence of APC (p=0.047). There were 57% positive APC tumours that were lymphovascular invasion (LVI) positive compared to 42.9% negative APC tumours that were LVI positive (p=0.015). With increasing T-stage, more CRC participants were PIK3CA negative (p=0.018). There was no association between the stage, grade, status, and tumour topography with APC, PIK3CA and SMAD4 mutation status. Conclusions: In Uganda, the frequency of APC mutations is similar, however, the frequencies of PIK3CA and SMAD4 mutations were higher than that reported in the Western world. APC mutations were associated with a positive LVI status. However, APC, PIK3CA, and SMAD4 mutations were not associated with most clinicopathological parameters.